Pengaruh Disiplin, Motivasi Kerja, Dan Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Niceso Sukses Indonesia Cabang Rempoa - Felicia Khalkali Hendris; Syifa Nuraiyini Amelia; Ila Florencia Soka Raga; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine and investigate the influence of work discipline, work motivation, and leadership style on the performance of employees of PT NICESO Sukses Indonesia Rempoa branch. There are 30 representatives of PT NICESO Sukses Indonesia Rempoa branch who were sampled in this study. The distribution of questionnaires and other documents to the performance of PT NICESO Sukses Indonesia Rempoa branch is important and optional information used in this study using an irregular examination strategy. Based on the findings, work discipline has a positive and significant influence on employee performance. However, work motivation and leadership style do not affect employee performance. Keywords: Work Discipline; Work Motivation; Leadership Style; Employee Performance